Using the canine microbiome to bridge translation of cancer immunotherapy from pre-clinical murine models to human clinical trials - Kleber, Kara T.; Iranpur, Khurshid R.; Perry, Lauren M.; Cruz, Sylvia M.; Razmara, Aryana M.; Culp, William T. N.; Kent, Michael S.; Eisen, Jonathan A.; Rebhun, Robert B.; Canter, Robert J. (Frontiers in Immunology, 2022)
The microbiome has clearly been established as a cutting-edge field in tumor immunology and immunotherapy. Recent studies demonstrate that response to checkpoint immunotherapies may be conferred or eliminated through gut microbiome modulation. Observations in murine models have highlighted the importance of the microbiome in response to therapy, yet these models have limitations that prevent a complete understanding of the underlying mechanisms. Dogs represent an important translational opportunity for studies of the cancer-immunity cycle, including microbiome studies. Dogs are diagnosed with naturally occurring cancers that are clinically and genetically similar to humans. Additionally, humans and dogs have similarities in both the development and composition of their microbiome. As companion animals, dogs inhabit the same environment as humans, a crucial factor in microbiome science. Finally, canines have increasingly available immunotherapies for cancer and undergo robust clinical trials. In this review, we will discuss the successes and limitations of the murine model and review the advantages of the canine microbiome as a bridge between pre-clinical mechanistic studies and human trials to fully unlock the potential of the microbiome as a diagnostic and therapeutic target in cancer.